(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluation the treatment results of pregnant women with mild Covid-19 at Ha Noi Obstetrics and Gynecology Hospital. Materials and method: A retrospective cross-sectional study was conducted, involving 1261 pregnant women with Covid-19 infection at Ha Noi Obstetrics and Gynecology Hospital from December 2021 to April 2022. Of these, 1119 patients were diagnosed with mild Covid-19 . Results: The maternal age were mainly in the 19-35-year-old group (85.9%). The gestational age at admission was above 37 weeks (81.1%). 45.6% received one or more vaccinations, 69.4% had mild symptoms. However, 69.1% had D-Dimer levels below 3500 ng/L and 66.9% had fibrinogen <6 g/L. Most did not require respiratory support (93.8%), but were given antibiotics (96.7%) and anticoagulants (100%). 78.3% were required to terminate the pregnancy immediately, mainly with elective caserean section and above 37 gestational weeks. The prevalance of postpartum complications was 8.5%. Conclusion: Pregnant women with mild Covid-19 exhibit few mild symptoms or no symptoms and no significant laboratory changes. Most only require non-specific management (antibiotics, anipyretics or antitussives therapy), but the termination is prioritized for cesarean section. It is important to plan vaccination to alleviate symptoms and complications of Covid-19.